Systematic Literatur Review: Implementasi Buku Saku Mini Games terhadap Hasil Belajar Matematika SD - Anggun Siska Pratiwi; Nelly Ainun Muna; Muhammad Sadam Husein; Muhammad Nofan Zulfahmi (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study examines the application of mini-game-based pocket books as a learning medium to improve elementary school (SD) students' mathematics learning outcomes. The background of this study is based on the challenges faced by students in understanding mathematical concepts effectively, so an innovative and fun approach is needed. Mini-game pocket books offer an interactive and motivating learning method, combining educational games with academic concepts. This study uses the systematic literature review (SLR) method by analyzing scientific articles published in the last five years from national journals and books. The analysis process is carried out descriptively to identify research patterns, the effectiveness of learning media, and their impact on student learning outcomes. The results of the study are expected to show that mini-game pocket books are able to improve students' conceptual understanding, learning motivation, and critical thinking skills. These findings also provide insight for teachers and researchers in developing more effective and interesting learning strategies at the elementary school level.